Osteochondroma of the Mandible: A Rare Case Report - Donepudi Nanda Kishore; H. R. Shiva Kumar; K. V. Umashankara; Kirthi Kumar Rai (Hindawi Limited, 2013)
Osteochondroma, also known as osteocartilaginous exostosis is a benign cartilage forming tumor that usually develops in long bones and relatively uncommon in the craniofacial region. Both the condyle and coronoid tip being the most common sites of occurrence in the mandible, it rarely appears at the symphysis region. Here, we describe a case of osteochondroma arising from the left parasymphysis of mandible.